Health Information, Treatment, and Worker Productivity : Experimental Evidence from Malaria Testing and Treatment among Nigerian Sugarcane Cutters - Dillon, Andrew; Friedman, Jed; Serneels, Pieter (World Bank Group, Washington, DC, 2014)
Agricultural and other physically demanding sectors are important sources of growth in developing countries but prevalent diseases such as malaria adversely impact the productivity, labor supply, and choice of job tasks among workers by reducing physical capacity. This study identifies the impact of malaria on worker earnings, labor supply, and daily productivity by randomizing the temporal order at which piece-rate workers at a large sugarcane plantation in Nigeria are offered malaria testing and treatment. The results indicate a significant and substantial intent to treat effect of the intervention -- the offer of a workplace-based malaria testing and treatment program increases worker earnings by approximately 10 percent over the weeks following the offer. The study further investigates the effect of health information by contrasting program effects by workers' revealed health status. For workers who test positive for malaria, the treatment of illness increases labor supply, leading to higher earnings. For workers who test negative, and especially for those workers most likely to be surprised by the healthy diagnosis, the health information also leads to increased earnings via increased productivity. Possible mechanisms for this response include selection into higher return tasks within the plantation as a result of changes in the perceived cost of effort. A model of the worker labor decision that allows health expectations partly to determine the supply of effort suggests that, in endemic settings with poor quality health services, inaccurate health perceptions may lead workers to suboptimal labor allocation decisions. The results underline the importance of medical treatment, but also of access to improved information about one's health status, as the absence of either may lead workers to deliver lower effort in lower return jobs.